Text of Bengu Mati: Social Semiotics of Systemic Functional Linguistics - I Ketut Suardana (International Journal of Systemic Functional Linguistics, 2020)
Text of Bengu Mati is one one Balinese written text used to educate Balinese community members. The moral values of the text cannot be comprehended well so that the text is not popular in the communities. Even, the young generations have preference to switch their entertainment modes into the modern entertainment mode. From that phenomenon, this research explored the social semiotics of the text. The theory used to analyze the text is the theory of social context from Systemic Functional linguistics, namely: context of situation, context of culture, and ideology (Halliday and Ruqaiya, 1999). The data source was taken from Kumpulan Satua ‘Balinese folklore’ written by Suwija, et.al (2019). This is qualitative research by applying library technique. The technique to collect the data was field, tenor, and mode, namely: what word was conceptualized, what action was actualized, who spoke, to whom spoke, how to speak, and others. The data are presented in two languages, Balinese language is used as the source language, and the English is used as the translation. The result of the research suggested that it is very important to comprehend social phenomenon based on social context. Without understanding the social context, it will destruct not only for the actor, but it is also for others. Be good person in front of the children is must since our behavior will be imitated and kept permanently in the mind by the children.